Comparison of Compudose, Ralgro and Synovex-S implants for growing steer calves - Simm, D.; Kuhl, Gerry L.; Schalles, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four field trials were conducted to compare Ralgro, Synovex-S and Compudose implants for growing steer calves. All implant programs significantly increased (P<.01) average daily gain. Reimplanting with Ralgro or Synovex-S improved gain an additional 5.6% compared to the average of these implants used singly and 4.8% compared to Compudose.
Keywords: Beef; Implants; Steers; Rate of gain